Factores para el estudio de la relación entre el grado de control familiar y el desempeño organizacional de las MIPyMEs familiares en el Área Metropolitana de Monterrey (Factors for the study of the relationship between the degree of family control and organizational performance of family MSMEs in Monterrey Metropolitan Area) - Peña Hinojosa, Armando Carlos; Mendoza Gómez, Joel (Facultad de Contaduría Pública y Administración U.A.N.L., 2012)
Abstract: The motors that move and drive the economies and societies of any country are the strength of the companies and might of the owners. At present, the importance of familyowned micro, small and medium sized companies is well known within the economies of the different Latin American and Caribbean countries; although, it is impossible to quantify exactly, the MSMEs are a key component in the contribution of economic growth, competitiveness, innovation, and in the generation of employment in any country; consequently, many governments and private institutions have initiated programs to promote this enterprising segment. It is not any different here in Mexico, as the above mentioned companies provide 50% of total employment and, in addition, 90% are family owned. This is where family influence or control becomes one of the important factors that have been proposed by the scientific academia as determining the organizational performance of a company. Based on this premise, the main topic of this article is to examine how the degree of family control affects the performance of said companies.